2021
DOI: 10.1111/jam.14906
|View full text |Cite
|
Sign up to set email alerts
|

Role and mechanism of action of butyrate in atherosclerotic diseases: a review

Abstract: Butyrate is a bioactive molecule produced by the intestinal flora and plays a major role in a variety of inflammatory diseases. Increasing evidence indicates that butyrate can regulate the occurrence and development of atherosclerosis. Coincidentally, it reduces hyperlipidemia and hyperglycemia, which are major risk factors of atherosclerosis. However, the mechanism by which butyrate regulates the development of atherosclerosis remains unclear. In this article, we review the effect of butyrate treatment on ath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 81 publications
(123 reference statements)
0
8
0
Order By: Relevance
“…In general, butyrate's inhibitory effect was seen in apolipoprotein B-48 output, TG export and chylomicron and VLDL secretion (79). Moreover, butyrate significantly reduced cholesterol synthesis by decreasing 3hydroxy-3-methylglutaryl coenzyme A reductase (HMG-CoA reductase) levels in the liver microsomes of rats (80). It is suggested that the reverse cholesterol transport system played a significant role in atherosclerosis progression, stimulating the cholesterol movement from the peripheral tissues to the liver for re-use or excretion into the bile acid and by upregulating cytochrome P450 7A1 (81).…”
Section: Butyrate and Lipid Metabolism Disordersmentioning
confidence: 99%
“…In general, butyrate's inhibitory effect was seen in apolipoprotein B-48 output, TG export and chylomicron and VLDL secretion (79). Moreover, butyrate significantly reduced cholesterol synthesis by decreasing 3hydroxy-3-methylglutaryl coenzyme A reductase (HMG-CoA reductase) levels in the liver microsomes of rats (80). It is suggested that the reverse cholesterol transport system played a significant role in atherosclerosis progression, stimulating the cholesterol movement from the peripheral tissues to the liver for re-use or excretion into the bile acid and by upregulating cytochrome P450 7A1 (81).…”
Section: Butyrate and Lipid Metabolism Disordersmentioning
confidence: 99%
“…Butyrate is a short-chain fatty acid essential to the host immune homeostasis and a major energy source for intestinal epithelial cells [56]. The most abundant butyrate-producing organisms are Clostridium, Eubacterium, Fusobacterium, and Bifidobacterium [57][58][59]. The depletion of butyrate-producing organisms contributes to intestinal EBD and upregulated inflammatory responses in the body.…”
Section: The Microbiome and Cardiovascular Diseasementioning
confidence: 99%
“…Higher F/B ratio and elevations in Enterobacteriaceae have been associated with depleted quantities of butyrate-producing organisms, increased systemic inflammation, and stroke [60]. A diet high in fiber promotes butyrate-producing organism growth and has been shown to stabilize plaque size in atherosclerosis [59]. Heart failure and coronary artery disease have also been associated with a reduction in butyrate-producing organisms [59,61].…”
Section: The Microbiome and Cardiovascular Diseasementioning
confidence: 99%
See 2 more Smart Citations